The Orphanage. Issue 2 (August 2021) - Hertz-Ohmes, Peter
Abstract : 'The Orphanage', by Peter Hertz-Ohmes, is a creative piece extracted from a longer work of the same name currently in completion. Voice and the play of memory are key aspects of a text richly concerned with the politics of exile, disaffiliation and naming.